Review: The marzēah in the Prophetic Literature. References and Allusions in Light of the Extra-Biblical Evidence - Joyce, Paul M. (The journal of theological studies, 2003)
The marzēah in the Prophetic Literature. References and Allusions in Light of the Extra-Biblical Evidence. John L. McLaughlin Pp. xviii+264 (Supplements to Vetus Testamentum, 86.) Boston/Leiden/Köln Brill 2001 90 04 12006 8 € 73/$90